Understanding the Web of Life: The Birds, the Bees, and Sex with Aliens - Tylianakis, Jason M (Public Library of Science, 2008)
Interactions in food webs indicate the structure and stability of ecosystems. Now, new research uses these interactions to illustrate the vulnerability of pollination webs to invasive plants and pollinators.